Environmental Change and Disease Dynamics: Effects of Intensive Forest Management on Puumala Hantavirus Infection in Boreal Bank Vole Populations - Voutilainen, Liina; Savola, Sakeri; Kallio, Eva Riikka; Laakkonen, Juha; Vaheri, Antti; Vapalahti, Olli; Henttonen, Heikki (PLOS ONE, 2012)
Intensive management of Fennoscandian forests has led to a mosaic of woodlands in different stages of maturity. The main rodent host of the zoonotic Puumala hantavirus (PUUV) is the bank vole (Myodes glareolus), a species that can be found in all woodlands and especially mature forests. We investigated the influence of forest age structure on PUUV infection dynamics in bank voles. Over four years, we trapped small mammals twice a year in a forest network of different succession stages in Northern Finland. Our study sites represented four forest age classes from young (4 to 30 years) to mature (over 100 years) forests. We show that PUUV-infected bank voles occurred commonly in all forest age classes, but peaked in mature forests. The probability of an individual bank vole to be PUUV infected was positively related to concurrent host population density. However, when population density was controlled for, a relatively higher infection rate was observed in voles trapped in younger forests. Furthermore, we found evidence of a “dilution effect” in that the infection probability was negatively associated with the simultaneous density of other small mammals during the breeding season. Our results suggest that younger forests created by intensive management can reduce hantaviral load in the environment, but PUUV is common in woodlands of all ages. As such, the Fennoscandian forest landscape represents a significant reservoir and source of hantaviral infection in humans.